Artificial Intelligence and Predictive Analytics in Nursing Care: Advancing Decision-Making through Health Information Technology - Alsaeed, Khalid Abdullah Saeed; Almutairi, Manal Turki Ali; Almutairi, Salman Mohammed Dughayyim; Al Nawmasi, Meshal Samah; Alharby, Nawaf Abdullah; Alharbi , Mohammad Masafr; Alazzmi, Mohammed Saud Sad; Alsalman , Adel Hamad; Alenazy, Fahad Ayed; Alfalaj, Falaj Ibrahim (Journal of Ecohumanism, 2024)
Background: Artificial intelligence (AI) and predictive analytics are transforming nursing care by improving decision-making processes and enhancing patient outcomes. This study examines the integration of AI technologies within nursing practice, emphasizing their potential to support nurses in delivering high-quality care. Methods: A comprehensive literature review was conducted to identify key applications of AI in nursing, including machine learning algorithms for risk assessment, natural language processing for documentation, and predictive analytics for patient outcomes. Results: Results indicate that AI tools can significantly reduce the administrative burden on nurses, allowing them to focus more on direct patient care. Additionally, the review highlights ethical, legal, and social implications associated with the adoption of AI technologies in nursing, such as the need for bias mitigation and ensuring patient privacy. Furthermore, the necessity for nursing education to incorporate AI competencies is emphasized, as current curricula often lack adequate training in health informatics and AI. Conclusions: In conclusion, while AI presents substantial opportunities to enhance nursing practice and patient care, it also poses challenges that must be addressed through comprehensive education and ethical frameworks. Future research should explore the long-term impact of AI on nursing roles and patient outcomes, ensuring that technology complements rather than replaces the human elements of nursing care.